Acinetobacter baumannii: human infections, factors contributing to pathogenesis and animal models. Issue 2 (18th June 2012) - McConnell, Michael J.; Actis, Luis; Pachón, Jerónimo
Abstract: Acinetobacter baumannii has emerged as a medically important pathogen because of the increasing number of infections produced by this organism over the preceding three decades and the global spread of strains with resistance to multiple antibiotic classes. In spite of its clinical relevance, until recently, there have been few studies addressing the factors that contribute to the pathogenesis of this organism. The availability of complete genome sequences, molecular tools for manipulating the bacterial genome, and animal models of infection have begun to facilitate the identification of factors that play a role in A. baumannii persistence and infection. This review summarizes the characteristics of A. baumannii that contribute to its pathogenesis, with a focus on motility, adherence, biofilm formation, and iron acquisition. In addition, the virulence factors that have been identified to date, which include the outer membrane protein OmpA, phospholipases, membrane polysaccharide components, penicillin‐binding proteins, and outer membrane vesicles, are discussed. Animal models systems that have been developed during the last 15 years for the study of A. baumannii infection are overviewed, and the recent use of these models to identify factors involved in virulence and pathogenesis is highlighted. Abstract : This review describes the characteristics of A cinetobacter baumannii that have contributed to its emergence as a medically important human pathogen and the animal model systems that have been developed for studying this organism.